Clostridioides difficile infection in neurosurgical patients in a national centre over 10 years: less common but associated with longer hospital stays - Skally, Mairead; Leonard, Maeve; O’Halloran, Philip J.; Husien, Ben; Bennett, Kathleen; Burns, Karen; Dinesh, Binu; Humphreys, Hilary; Fitzpatrick, Fidelma (Acta neurochirurgica, 2023)
Background Clostridioides difficile infection (CDI) is a leading cause of healthcare-associated (HA) diarrhoea, contributing to patient morbidity and prolonged length-of-stay (LOS). We retrospectively assessed CDI over a decade in a national neurosurgical centre, with a multi-disciplinary approach to CDI surveillance and antimicrobial stewardship, by comparing CDI patients with other patient groups. Methods Data on CDI in neurosurgical inpatients between January 2012 and December 2021 were collated. Disease-specific variables were compared to other inpatients with CDI. Rates per 10,000 bed days used were calculated. Patient-specific differences were compared with neurosurgical patients without CDI. CDI rates by patient group were explored using odds ratio (OR) and χ 2 analyses. Negative binomial regression was used to investigate CDI rates over time. Results Of 50 neurosurgical patients with CDI, all were HA; the average age was 53 years (standard deviation (SD) 16.3 years), 49 were first-episode CDI, and three had severe CDI. The majority (76.7%) had received recent antimicrobials. Compared with non-neurosurgical CDI patients, neurosurgical CDI rates differed significantly (1.9 versus 3.6 per 10,000 bed days used, p < 0.05), neurosurgical patients were younger ( p ≤ 0.01), C. difficile testing was more likely to be requested by neurosurgeons (OR 2.4; p ≤ 0.01), and the proportion of severe CDI was higher (6% versus 2%, OR 3.0, p = 0.07, confidence interval (CI) 0.54 to 11.3). Within the neurosurgical cohort, CDI patients had an average LOS four times that of other patients (CI 15.2 to 35.1; p < 0.01) and were older (53.5 versus 47.8 years, CI 0.1 to 11 years; p < 0.05). Only one CDI outbreak was linked to neurosurgical patients. Conclusion CDI in neurosurgery patients differed from the wider hospital, with greater awareness of CDI testing. Longer LOS impacted bed utilisation with limited capacity. Robust surveillance supports proactive antimicrobial stewardship programmes in this vulnerable population.